Optimal K-Node Set Reliability with Capacity Constraint of Distributed Systems, Via a Heuristic Algorithm - Chiu, Chin-Ching; Yeh, Yi-Shiung (Malaysian Journal of Computer Science, 2002)
In this work, we present a heuristic method to reduce the computational time and the absolute error from the exact solution for obtaining a k-node set with capacity constraint. This method uses an efficient objective function to select an adequate node when deriving the k-node set process. Reliability computation is performed only once, thereby spending less time to compute the reliability. Moreover, the absolute error of the proposed algorithm from exact solution is smaller than that of k-tree reduction method. Computational results demonstrate that the proposed algorithm is a more efficient solution for a large distributed system then conventional ones.